The Implementation of Clean Water Service Provider PERUMDAM Tirta Kencana Jombang Regency - Rahmawati, Biwin; Manggalou, Singgih (Jurnal Kebijakan Publik, 2025)
Water resources are part of limited natural resources both in terms of quality and quantity in meeting human needs. The existence of Regional Drinking Water Company (PERUMDAM) has a strategic role in ensuring the distribution of clean water evenly, considering its urgency for various sectors of life. PERUMDAM Jombang Regency, as one of the Regional Owned Enterprises (BUMD) in Indonesia, seeks to carry out this function. However, the services provided still face obstacles, especially for people who rely heavily on the provision of drinking water, so the implementation is not fully optimal. Like the number of customer reports received by Tirta Kencana Regional People's Representative Council. This study used a qua-litative approach using descriptive methods, referring to George C. Edward III's theory of policy implementation, which includes four main variables: communica-tion, resources, disposition, and bureaucratic structure as major references in identifying the results of this study. Data collection techniques include interviews, observations, and documentation. Research results show that clean water services are running quite successfully, as shown by the availability of clear SOPs and the good attitude of employees. However, there are still obstacles in terms of information clarity and limitations in maintaining the water distribution network. This finding emphasizes the need to improve communication and optimize infrastructure to improve the quality of clean water services for the community.